Effects of long-term intake of iron-enriched beverage containing ʟ-ascorbic acid 2-glucoside on iron nutrition status and condition of female college athletes - Megumi Matsumoto; Tsukasa Saruta; Shiori Aizawa; Satoko Uchida; Hidehiko Kushi (Japanese Society of Physical Fitness and Sports Medicine, 2022)
In female athletes, iron deficiency and anaemia have marked effects on performance and could also impair health. Female athletes often limit their diet to control their weight, and thus may not obtain sufficient iron. Iron is difficult to absorb, so it is necessary to devise an efficient intake method. Absorption of non-haem iron seems to increase when taken with ʟ-ascorbic acid (vitamin C [VC]). ʟ-Ascorbic acid 2-glucoside (VCG), a food additive that binds glucose and thus improves its stability, is often added to beverages. Therefore, the effects of simultaneous intake of iron and VCG on iron nutrition were examined in female athletes. The subjects were 41 female college student athletes, and a placebo test was conducted in which a drink containing 200 mg VCG and 6 mg iron was consumed twice daily for 2 months. The placebo group consumed only the iron without VCG. Iron nutrition status was evaluated by blood tests, dietary surveys and subjective symptoms before and after the 2 months. Blood tests were also performed to determine the effects of iron intake on liver function and hepcidin levels. After 2 months, the VCG/iron drink had increased serum iron and blood VC levels in the VCG group compared to the placebo group. By contrast, aspartate aminotransferases (AST) tended to decrease in the VCG group, and no increase in hepcidin was observed in either group. This suggests that long-term iron intake through beverages can improve iron nutritional status in female athletes, and that VCG may enhance this status by suppressing the oxidative damage to the liver associated with iron intake.